Strengthening the Panca Budhi Indriya through Local Wisdom for the Competitiveness of Tourism MSMEs - I Gusti Putu Agung Widya Goca; Ni Nyoman Sudiyani; Putu Gede Denny Herlambang; Luh Ayu Susila Wati; Khoirunnisa Etta Argiatna (Penerbit Goodwood, 2026)
Purpose: This study aims to develop a model that links the local wisdom values of Panca Budhi Indriya with innovation capability to improve the competitive advantage of tourism SMEs in Bali. This study focuses on how cultural values foster innovation and strengthen market positioning. Methodology/approach: The study will be conducted in three districts/cities in Bali, involving 150 tourism SMEs in the culinary, handicraft, and local accommodation sectors. A quantitative approach with an explanatory survey design was used. Data will be collected through questionnaires developed from the literature and validated by experts. Structural Equation Modeling (SEM) with SmartPLS or AMOS will be applied to test relationships and mediation effects. Results/findings: The expected results are as follows: (1) local wisdom values have a significant positive effect on innovation capability; (2) innovation capability enhances competitive advantage; and (3) innovation capability mediates the relationship between local wisdom and competitive advantage. This study generates a tested conceptual model of culture-based SME competitiveness. Conclusions: Panca Budhi Indriya, as part of Balinese cultural heritage, represents not only tradition but also a strategic resource that strengthens competitiveness when integrated with innovative capability. Limitations: The study is limited to SMEs in the tourism sector in Bali and relies on self-reported data, which may contain biases. Contributions: This study enriches the Resource-Based View (RBV) theory from a cultural perspective and provides practical guidance for SMEs, policymakers, and tourism programs to integrate cultural values into innovation strategies.